The impact of Algerian University graduates on Algeria’s gross domestic product - Maache, Fethi; Amari, Houcin; Zaoui, Aissa (International journal of economic perspectives, 2024)
This study aims to measure the number of university graduates in order to provide a meaningful representation of the state of higher education in Algeria during the study period. Using a simple linear model, the study examines both the concept and the objectives of higher education, alongside an analysis of the current reality of higher education. It also examines whether there is a relationship between the number of university graduates and gross domestic product (GDP). The results indicate a positive correlation between the two variables, suggesting that higher education plays a fundamental role in driving progress and direction, given its responsibility for training the workforce necessary for development in various sectors.